A Study to Assess the Knowledge and Attitude of Adolescence Regarding Computer Vision Syndrome in Selected School Of Dehradun, India - Dewan, Pramila; Maletha, Archana; Bhandari, Bhawana; Lama, Asta (Journal of Advanced Academic Research, 2023)
Background: Computer Vision Syndrome is one of the rising health concerns related to technology (cell phones and tablets) due to continuous use of computers among adolescents. Almost 75% of a person’s daily activities include computer usage. Globally, around 60 million computer workers experience discomfort from Computer Vision Syndrome. Nearly 45 million workers use computers by starring at the screen for hours continuously. Objectives: The objective of this study is to assess Knowledge and Attitude of Adolescence Regarding Computer Vision Syndrome in Selected School of Dehradun, India. Methodology: A quantitative, descriptive, cross-sectional research design is used for this study. The total sample size for the study was 120 adolescents. Non-probability convenience sampling technique was used for the study. The collected data were analyzed and interpreted using descriptive and inferential statistics using SPSS (Version 20.0) software. Result: More than half of the respondents (50.8%) had inadequate knowledge and it revealed that highest 69.2% of them had a negative attitude on computer vision syndrome. There is a significant association between knowledge score with the selected variables like age in years, education and types of electronic device. There is a significant association between attitudes with the area of residence. There is also a positive correlation between knowledge and attitude ("r" value of 0.519). Conclusion: More than half of respondents had inadequate knowledge and it also revealed that majority of them had a negative attitude on computer vision syndrome.